PENGARUH NILAI TUKAR DAN NET EKSPOR TERHADAP CADANGAN DEVISA INDONESIA - Inggrid Puspita Rini; Juliansyah Juliansyah; Agus Junaidi (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
This study aims to determine the effect of exchange rates and net exports on Indonesia's foreign exchange reserves in 1999-2018. The sample in this study amounted to 20 data that will be used as research objects. The dependent variable in this study is the Indonesian Foreign Exchange Reserves, while the independent variables are the exchange rate and net exports. To see the influence between variables, researchers used an analysis tool that is by testing multiple linear regression also tests the classical assumptions.